2020
DOI: 10.31728/jnn.2020.00093
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Changes in Systemic Blood Viscosity and Transcranial Doppler Pulsatility in Lacunar Stroke

Abstract: Background:We hypothesized that changes in blood viscosity (BV) would influence cerebral vessel viscosity, which is related to the transcranial Doppler (TCD) pulsatility index (PI). Using serial BV and TCD examinations, we sought to evaluate the relationship between changes in BV and TCD PI in lacunar stroke patients. Methods: Patients (aged ≥50 years) who developed lacunar stroke within 7 days of symptom onset were enrolled. Laboratory tests and TCD examinations were conducted at admission and 180 (±30) days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Long-term increase in blood lipids can also cause damage to the artery walls, which correlates viscosity with atherosclerosis. In this study, the hematocrit at the time of examination was not analyzed so that it might also affect the results of the PI indirectly (Kim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term increase in blood lipids can also cause damage to the artery walls, which correlates viscosity with atherosclerosis. In this study, the hematocrit at the time of examination was not analyzed so that it might also affect the results of the PI indirectly (Kim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The microangiopathic process also releases several inflammatory cytokines, such as endothelin and prostacyclin, and interferes with autoregulation of cerebral blood flow, which impairs blood flow to distal areas. Vicenzini et al have found that an increase in PI is associated with a decrease in end-diastolic volume (EDV), which indicates the development of vasoconstriction in the distal vessels (Kim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…BV is elevated in the acute phase of ischemic stroke and gradually improves in the chronic phass, 7 and appears to be significantly higher in LS than in other stroke subtypes. 9,11 When the blood passes through the stenotic cerebral perforating arteries, increased BV can aggravate the flow disturbance and cause vascular endothelial remodeling and luminal occlusion. These hemorheological changes can be related to thrombus propagation or arterial reocclusion in progressive LS.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 It has been postulated that when the blood passes the cerebral small arteries, increased BV can aggravate the flow disturbance and cause luminal occlusion. 9,11 Considering the underlying pathomechanisms of ND in LS, we hypothesized that increased BV could influence cerebral vessel viscosity, which is related to thrombus propagation and collateral blood flow circulation. Hence, this study aimed to determine the relationship between ND and BV in patients with LS.…”
Section: Introductionmentioning
confidence: 99%
“…High BV increases accordingly thromboembolic risk and is a correlation factor for cardiovascular disease. Those studies exhibit the associations between BV and ischemic stroke (Grotemeyer, Kaiser, Grotemeyer, & Husstedt, 2014; Han et al, 2019; T. Kim et al, 2020). There are many comprehensive factors to effective BV, such as blood sugar, erythrocyte amounts and thrombus (Baeckström, Folkow, Kendrick, Löfving, & ÖBerg, 1971; Cadroy, Horbett, & Hanson, 1989;Somer & Meiselman, 1993;Tamariz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%